2021
DOI: 10.1111/apm.13192
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin‐1 in breast cancer

Abstract: The canonical function of aquaporin (AQP) water channels is to facilitate passive transport of water across cellular membranes making them essential in the regulation of body water homeostasis. Moreover, AQPs, including AQP1, have been found to be overexpressed in multiple cancer types, including breast cancer, where AQP1 overexpression is associated with poor prognosis. AQPs have been shown to affect cellular processes associated with cancer progression and spread including cell migration, angiogenesis, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…Bystrup [ 107 ] considers that understanding the underlying molecular mechanisms of how AQP5 contributes to cancer development and progression is crucial for the potential use of AQP5 as a prognostic biomarker and for the development of targeted intervention strategies for the treatment of breast cancer patients. A similar observation was presented by Traberg-Nyborg [ 108 ] on aquaporin-1 and by Milkovic [ 109 ] on aquaporins 3 and 5. In addition to the above-mentioned statement, a study by Moosavi [ 110 ] found that overexpression of AQP1, AQP3, and AQP5 is inextricably linked to carcinogenesis, metastasis, decreased survival rate, lymph node metastasis, a worse prognosis, and cellular migration and that furthermore, cancer therapies associated with these markers suggest AQP decreases during treatment.…”
Section: Resultssupporting
confidence: 87%
“…Bystrup [ 107 ] considers that understanding the underlying molecular mechanisms of how AQP5 contributes to cancer development and progression is crucial for the potential use of AQP5 as a prognostic biomarker and for the development of targeted intervention strategies for the treatment of breast cancer patients. A similar observation was presented by Traberg-Nyborg [ 108 ] on aquaporin-1 and by Milkovic [ 109 ] on aquaporins 3 and 5. In addition to the above-mentioned statement, a study by Moosavi [ 110 ] found that overexpression of AQP1, AQP3, and AQP5 is inextricably linked to carcinogenesis, metastasis, decreased survival rate, lymph node metastasis, a worse prognosis, and cellular migration and that furthermore, cancer therapies associated with these markers suggest AQP decreases during treatment.…”
Section: Resultssupporting
confidence: 87%
“…Excessive RONS absorbed by AQPs can induce nitro-oxidative stress within the cell, leading to damage to intracellular biomolecules and signaling pathways, ultimately resulting in cell death [ 212 ]. AQPs are often overexpressed in various types of cancer cells, including breast [ 213 , 214 ], lung [ 215 ], ovarian [ 216 , 217 ], and colorectal cancer [ 218 , 219 ]. This overexpression allows AQPs to increase the intracellular RONS level in cancer cells compared to normal cells, making CAP more detrimental to cancer cells than to normal cells [ 220 , 221 ].…”
Section: Non-reactive MD Simulations Of Proteinsmentioning
confidence: 99%
“…Leptin-upregulated AQP1 protein expression was inhibited by treatment with OB-R BP (Figure 4E,F) and AG490 (Figure 4G,H), indicating that AQP1 is upregulated by the leptin/Ob-R/STAT3 pathway. High AQP1 expression affects the cellular processes including cell migration, proliferation, and angiogenesis [48]. Overexpression of AQP1 using the activation plasmid (Figure 5A,B) effectively increased VM (Figure 5C,D) and upregulated the expression of VM-related proteins (Figure 5E,F), indicating that AQP1 itself could induce VM.…”
Section: Discussionmentioning
confidence: 98%